Description of three new genera, Paratibicen, Gigatibicen, and Ameritibicen, of Cryptotympanini (Hemiptera: Cicadidae) and a key to their species - Young June Lee (Journal of Asia-Pacific Biodiversity, 2016)
Three new genera, Paratibicen gen. nov., Gigatibicen gen. nov., and Ameritibicen gen. nov., are erected for the former members of Neotibicen Hill & Moulds, 2015 from North America, designating Cicada similaris Smith & Grossbeck, 1907, Cicada auletes Germar, 1834, and Cicada dorsata Say, 1825 as their respective type species. Morphological comparisons are made among the three new genera, Lyristes Horváth, 1926 (= Tibicen Latreille, 1825), Auritibicen Lee, 2015, Neotibicen sensu stricto, and other related genera. A key to the species of the genera Neotibicen, Paratibicen, Gigatibicen, and Ameritibicen is provided.